Implementing free prior and informed consent: the United Nations Declaration on the Rights of Indigenous Peoples (2007), the challenges of REDD+ and the case for the precautionary principle. Issue 1 (7th February 2019) - Raftopoulos, Malayna; Short, Damien
ABSTRACT: Over 21 years after the United Nations Declaration on the Rights of Indigenous Peoples (September 2007 – hereafter UNDRIP) was passed, it is useful to examine the functionality and utility of a core principle it contains- the notion of Free Prior and Informed Consent (FPIC) with respect to the twin challenges of environmental destruction and a key 'mitigation' policy: REDD+. While UNDRIP, and to a lesser extent, the International Labour Organisation Convention No. 169 (ILO 169) has strengthened the legal status of FPIC, its application has proved to be extremely difficult. This article argues that when considering the potential harm of environmental and REDD+ climate change policies there needs to be a greater emphasis placed on the 'precautionary principle' when applying FPIC. Demonstrating why precaution needs to be taken in order to ensure human rights, this article argues that increasing the prominence of the precautionary principle within FPIC can impact significantly on the protection of biodiversity as well as the way in which environmental harm, laws and regulations are understood in relation to their social and cultural impact and shape future responses to the climate change crisis.